Legal application of the offence of murder and euthanasia in Nigeria - Salihu, Sani Ibrahim (Universiti Utara Malaysia Press, 2017)
Euthanasia is one of the concepts that stifled debate among academics, lawyers, religious scholars and even politicians.The reason being that it is killing human being although for compassionate reason, and with voluntary consent of the victim. Opponents of legalizing it, rely on the fear of slippery slope, sacred nature of life and question of inheritance. Despite the aforementioned factors, some countries legalised it while it remains a crime in the majority of other countries including Nigeria.We wrote this paper with the aim of highlighting and reinforcing the prohibition of the practice using Nigerian laws. Doctrinal method was employed to achieve the above objectives. In the process both primary and secondary legal materials were fully considered. The scope of the paper was limited to substantive provisions of both the penal code and the criminal code of Nigeria respectively.The aforementioned laws deal with the offence of murder by conduct or omission. However, there is no mention of the direct act of euthanasia, but from the reading of the laws inference can be drawn relating to withholding and withdrawing medical treatment leading to death. The finding of the paper is that although there is an elaborate provision regarding the prohibition of euthanasia under the criminal code, the law is not so adequate under the penal code and both laws are independent of themselves. Since both laws are applied at different geopolitical zones in Nigeria, the inadequacy of the laws will affect the administration of criminal justice in Nigeria. The paper therefore suggests an amendment to the penal code to fill the gap it has created.